Bridging the mobile internet gap a marketing plan for Smart Communications Inc. - Alvarez, Ma. Joan Bianca; Cruz, Edison (Quezon City University of the Philippines Diliman, 2013)
Mobile internet is one of the hottest fads in the field of mobile technology. Even the most basic handset available today provides access to the Internet, allowing consumers to use it for primary purposes like accessing the email and surfing the Internet. As of Q1 2012, only 5 percent of total SMART Communication subscribers avail and use SMART's mobile internet promos and offers. This paper will discuss the marketing strategy that can be adopted by the company such that it can reach a 20 percent penetration rate in 5 years.This paper used tools like the 10-step marketing planning process, S-curve analysis, Porter's 5 forces, Porter's Generic Competitive strategies, SWOT analysis and finally the 7Ps of Service Marketing to give a comprehensive strategy for SMART. This paper gave an analysis on the industry of mobile internet and factors that affect growth. By using frameworks like Marketing audit, Porter's 5 forces and SWOT, it was able to analyze the existing strategies of SMART. It provided a comprehensive discussion on the specific consumer needs that SMART's Mobile Internet service must address. The final output is a marketing strategy and marketing mix to increase adoption rate of current subscribers to 22M mobile internet users out of 55 million subscribers in 5 years. The consumer study shows that the target market can choose their purchases based on their lifestyle and at present, there is no one killer package that can push mobile internet. The key is to educate people on mobile internet, to increase awareness and push trial. SMART's overall communication and service delivery strategy will play a big part in pushing their business goals. In creating the marketing strategy of SMART for its mobile internet service, it is important to consider the current situation of the worldwide industry and give a snapshot of the current trends in the Philippine setting. While mobile internet is pervasive and highly immersive in more advanced countries like USA, in the Philippines, this service is still in its infancy/fermentation stage. The end goal is to create mobile internet products that can respond to the emerging trends, intense rivalry and ever-changing consumer needs of the Filipino mobile internet user.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Smart Communications Inc; Marketing research; Mobile internet gap; Marketing plan